The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cptc.202200237
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Bright Near‐Infrared Sulfonate‐Indolizine Cyanine‐ and Squaraine‐Albumin Chaperones: Record Quantum Yields and Applications

Abstract: The Front Cover shows a single near‐infrared dye being laser‐excited and dimly fluorescing in an aqueous biological environment compared to a near‐infrared dye bound to albumin fluorescing brightly in the same environment. Cover designed by Karina Kapusta. Read the full text of the Research Article at 10.1002/cptc.202200127.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…S9†, and SO3SQ ) were rigorously studied via computational protein docking. 12 In that study, the dyes were found to bind primarily to the heme cleft of HSA. A significant contributor in binding was the sulfonate indolizine moiety where both the indolizine heterocycle and sulfonate group appended to the heterocycle had distinct protein group binding.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…S9†, and SO3SQ ) were rigorously studied via computational protein docking. 12 In that study, the dyes were found to bind primarily to the heme cleft of HSA. A significant contributor in binding was the sulfonate indolizine moiety where both the indolizine heterocycle and sulfonate group appended to the heterocycle had distinct protein group binding.…”
Section: Resultsmentioning
confidence: 92%
“…Our group has previously reported an indolizine squaraine dye ( SO3SQ , Scheme 1) that demonstrates “ultra-bright” switch-on near infrared (NIR, 700–1000 nm) emission upon binding to albumin in fetal bovine serum (FBS), human serum albumin (HSA), and on latent blood stains. 11–13 Albumin has previously been shown to enhance dye emission for sensors and for in vivo biological imaging; however, these reports have not been found to be applicable in forensic imaging (Table S2†). 9,14–25 The albumin– SO3SQ complex displays longer lived emission (on the order of days to weeks), more selectivity for blood (since albumin is specific to and ubiquitous in blood), 26,27 and leaves DNA less perturbed than with oxidizing solutions or ultraviolet (UV, 100–400 nm) light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, cattle blood was used as the blood source since SO 3 SQ has shown the ability to detect both human and bovine albumin. 43…”
Section: Emission Of So 3 Sq With Bloodmentioning
confidence: 99%
“…The enhancement in uorescence of SO 3 SQ may derive from the disaggregation of dyes 41,42 and subsequently binding of monomeric SO 3 SQ to albumin. 43 The change in environment aer complexation with the HSA protein might also promote the high uorescent emission. To the best of our knowledge, there is no report on the latent bloodstain detection using NIR uorescent dyes with turn-on uorescent intensity enhancements.…”
Section: Introductionmentioning
confidence: 99%